2020
DOI: 10.1101/2020.07.27.219618
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Weak catch bonds make strong networks

Abstract: Molecular catch bonds are ubiquitous in biology and well-studied in the context of leukocyte extravasion1, cellular mechanosensing2,3, and urinary tract infection4. Unlike normal (slip) bonds, catch bonds strengthen under tension. The current paradigm is that this remarkable ability enables cells to increase their adhesion in fast fluid flows1,4, and hence provides ‘strength-on-demand’. Recently, cytoskeletal crosslinkers have been discovered that also display catch bonding5–8. It has been suggested that they … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…In reconstituted actin networks, studied in vitro, it was found that the mechano-sensitive ARP2/3 complex, which creates branch points in actin filaments, results in force-induced network densification and stiffening ( 61 ). Also, catch bonding cross-linkers, such as α-actinin, whose bonding strength with actin filaments grows under the action of mechanical stress, can result in force-gated accumulation and filament bundling ( 64 , 65 ). Cross-linking actin with these proteins does not result in aster formation, which implies that a more complex mechanism involving multiple regulators is at play in the mechanostat.…”
Section: Discussionmentioning
confidence: 99%
“…In reconstituted actin networks, studied in vitro, it was found that the mechano-sensitive ARP2/3 complex, which creates branch points in actin filaments, results in force-induced network densification and stiffening ( 61 ). Also, catch bonding cross-linkers, such as α-actinin, whose bonding strength with actin filaments grows under the action of mechanical stress, can result in force-gated accumulation and filament bundling ( 64 , 65 ). Cross-linking actin with these proteins does not result in aster formation, which implies that a more complex mechanism involving multiple regulators is at play in the mechanostat.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous experimental findings have highlighted the key role of actin cross-linkers as key regulators of actin cortex mechanics in cells. In addition, experimental evidence is increasing that actin cross-linker binding dynamics is by itself mechanosensitive [20][21][22][23][24] . Here, we investigated the influence of mechanosensitive molecular regulators on pattern formation and deformation of active spherical surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Motivated by experimental observations, see e.g. [21][22][23][24] , we anticipate that the unbinding rate of molecular regulators of active stress depends on the local trace of the in-plane stress t i i . In particular, we make the choice of a Bell model dependence…”
Section: Constitutive Equations For An Active Gel On a Curved Surface...mentioning
confidence: 99%
See 2 more Smart Citations